PENGARUH BRAND IMAGE AMBON CITY OF MUSIC TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE KOTA AMBON - Marcha Stephanie Inapratama Matitaputty; Meiti Leatemia (Jurnal Administrasi Terapan, 2022)
Ambon is a city in the eastern part of Indonesia which is called "Ambon Manise" and is known as the place where great musicians were born. Ambon has been declared to become a world Music City in 2011 and realized in 2019, various efforts, both thoughts, energy, materials provided by the Ambon City government, have made Ambon City successful in establishing itself and winning this title. This study aims to find out whether the branding of Ambon City of Music influences the tourists’ decision in visiting Ambon The type of research used is descriptive verification. The population in this study are all the characteristics of those who visit Ambon city. The sampling technique used is Nonprobability sampling by way of Incidental Sampling so that the sample obtained is 100 tourists visiting Ambon. Data analysis technique and hypothesis testing used is multiple regression method.The research results show that brand image has a significant effect on visiting decisions. The factor that most influences the decision to visit is the strength of brand associations, this is supported because the information entered into consumers' memories is very strong and that information survives as the brand image of Ambon City of Music, this aspect needs to be considered so that brand image of Ambon city of music can be optimized to increase the number of tourist in visiting Ambon.Keywords: Brand Image, Visit Decision